Learning Account Upgrading for Digital Management in Islamic Education 5.0: Peningkatan Akun Pembelajaran untuk Manajemen Digital dalam Pendidikan Islam 5.0 - Istiqomah, Nurul; HARYANTO, BUDI (Adabiyah: Jurnal Pendidikan Islam, 2025)
General background: The digital transformation in the 5.0 era requires Islamic educational institutions to adopt adaptive management systems. Specific background: The Indonesian government provides free learning accounts for students and teachers as part of this effort. Knowledge gap: While previous studies emphasize learning accounts in teaching and assessment, limited attention is given to their role in institutional management. Aims: This study investigates the implementation of learning account upgrading, its use in management, and the challenges faced by Islamic educational institutions. Results: Conducted at Al Fattah Islamic Boarding School, Sidoarjo, from December 18–31, 2023, using quantitative methods through observation, documentation, and interviews, findings show that 56.25% of users had activated their accounts. However, 71.3% of junior high students had not activated due to limited access to laptops and Chromebooks (2–5 users per device). Novelty: This research highlights how learning accounts are upgraded to support digitalized management beyond classroom use. Implications: Institutions are encouraged to strengthen digital infrastructure and provide socialization to maximize account utilization for sustainable management in the digital era. Highlights: Learning account upgrading extends beyond teaching into institutional management. Main obstacle: limited device availability among junior high students. Novel contribution: bridging management digitalization in Islamic boarding schools. Keywords: Learning Account; Upgrading; Islamic Education; Digitalization; Management